Of Sufficient Conditions of the Application oi the Monte-Carlo Method to Systems of Nonlinear Equations - Kleiza, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Клейза. О достаточных условиях применимости метода Монте-Карло для решения систем нелинейных уравненийV. Kleiza. Apie pakankamas netiesinių lygčių sistemų sprendimo Monte-Karlo metodu sąlygas